A Rational Approach to IrPTe – DFT and CalPhaD Studies on Phase Stability, Formation, and Structure of IrPTe1. Issue 6 (15th May 2015) - Pielnhofer, Florian; Schöneich, Michael; Lorenz, Tobias; Yan, Wenjie; Nilges, Tom; Weihrich, Richard; Schmidt, Peer
Abstract Phase formation, stability, crystal and electronic structures of IrPTe are investigated from experiment and quantum chemical calculations. The phase formation is studied from thermodynamic data and CalPhaD modeling. Applying a high‐temperature gas‐balance a formation pathway for IrPTe is studied from the elements and the binary parent compounds IrTe2 and IrP2. The obtained paracostibite (CoSbS) type structure contains rarely occurring heteroatomic P–Te dumbbells. The stability of IrPTe and the found structure is studied from DFT calculations with respect to the elements, IrTe2 and IrP2, and possible polymorphs. Probable metastable modifications with XY dumbbells (as known for isoelectronic compounds like CoAsS) are obtained from systematic DFT modelling. Phase transitions are predicted form the equation of states (EOS). According to its electronic band structure IrPTe is predicted as small gap (ΔEg = 0.5 eV) semiconductor.